Optical control of magnetization dynamics in Gd–Fe–Co films with different compositions. (12th September 2017) - Ohkochi, Takuo; Fujiwara, Hidenori; Kotsugi, Masato; Takahashi, Hirokazu; Adam, Roman; Sekiyama, Akira; Nakamura, Tetsuya; Tsukamoto, Arata; Schneider, Claus M.; Kuroda, Hiroto; Arguelles, Elvis F.; Sakaue, Mamoru; et al.
Abstract: Perpendicularly magnetized ferrimagnetic Gd–Fe–Co thin films with different compositions and multilayer arrangements were subjected to femtosecond laser pulses. The pulses triggered different magnetization dynamics in the various thin films. In the Gd26 Fe66 Co8 film, which has an angular-momentum-compensation temperature ( T A ) well above ambient temperature ( T exp ), monotonic magnetization reversal occurred, whereas the Gd22 Fe70 Co8 film (where T A is well below T exp ) exhibited remarkable wavelike spin modulation with spatial inhomogeneity during relaxation of the laser-induced nonequilibrium state. These findings can enable broad-range tuning of the magneto-optical responses of Gd–Fe–Co alloys, facilitating advances in materials engineering.